Pembatalan Putusan Arbitrase Ad Hoc di Indonesia: Analisis Putusan Mahkamah Agung dalam Sengketa Konstruksi - Sabitaqila Suma Farhaniatussafana; Tri Utami; Sawitri Yuli Hartati (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the legal foundation and judicial reasoning applied by the Supreme Court of Indonesia in reviewing requests for annulment of ad hoc arbitration awards in construction disputes, focusing on how judges interpret the limited grounds for annulment under Law No. 30/1999. The analysis demonstrates that the Court consistently upholds the principle of finality while maintaining a strict supervisory threshold to ensure that the arbitration process remains free from fraud, hidden documents, or procedural manipulation. Construction disputes, which frequently involve complex technical assessments and high contractual risks, require judges to evaluate whether the alleged violations genuinely undermine the legitimacy of the arbitral process rather than merely reflect dissatisfaction with the decision. Findings show a clear judicial pattern that prioritizes procedural integrity over substantive reconsideration of the dispute, aligning national jurisprudence more closely with prevailing international standards. This approach strengthens legal certainty for construction-sector stakeholders while reinforcing the credibility of ad hoc arbitration as an efficient dispute resolution mechanism in Indonesia.